Patients Characteristics, Pattern and Outcome of Major Limb Amputations from a Tertiary Hospital in Tanzania: A Retrospective Chart Review (Tanzania Medical Journal, 2022)
BackgroundAmputation of major extremities is a preventable problem of public health concern. Limb loss in resource-limited countries is associated with significant physical disadvantages to the patient and aggravates the social burden. This study aimed to characterize amputees and their immediate post-operative complications from a single center.MethodsA 19-months (January 2014 to August 2015) retrospective hospital-based chart review was conducted at Muhimbili Orthopedic Institute on all amputees.  A predesigned and pretested checklist was used to extract details on demography, reason for amputation, type of amputation, 30-day post-operative complication and mortality. Data was entered into SPSS version 20 for analysis where descriptive statistics were computed. Ethical clearance and permission to conduct the study was obtained from Muhimbili University of Health and Allied sciences Institutional Review Board Ref.No.2015-08-24/AEC/Vol. IX/352.ResultsA total of 77 patients who had amputation and whose files could be retrieved were involved in this study. The age range of the participants was 5 - 75 years (mean age of 32.2, SD 13.7). Majority, 87.1% were in the age group between 16 to 45 years. Male predominance was noted with male to female ratio of 3.5: 1. Trauma was the commonest all cause by 79.2%, and lower limbs led the log with lower to upper limb ratio of 2.9:1. Complications were reported in 25(32.5%) with stump infection being the leading by 22 (28.5%). Two deaths were reported of which all were from advance metastatic disease.ConclusionsTrauma was the leading cause of major extremity amputation in this study center. Majority of the amputees were male at their younger age. A quarter of the amputees developed complications with surgical site infection being the commonest.